1977
DOI: 10.1212/wnl.27.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan diabetic neuropathy

Abstract: Peripheral nerves of diabetic rats were studied 2 years after alloxan injection. We observed demyelination and remyelination, axonal degeneration and regeneration, reduplication of basal laminae around vessels and Schwann's cells, as well as onion bulb formation by proliferated Schwann's cells. Crystalline deposits composed of aggregates of fibrillary electron dense material often occurred in vessel walls and endoneurium of diabetic animals but rarely were seen in nerves from age-matched control animals. Glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 0 publications
3
34
0
1
Order By: Relevance
“…Basing on our observation, it allows us to consider that glycogen-like particles and electron homogeneous amorphous materials within the axons strongly suggest that metabolic abnormalities actually occur in the axons of the diabetic state. In experimental diabetic animals, accumulation of glycogen particles within mitochondria of the axons was found in the peripheral nerves of the rats rendered diabetic with alloxan for over 2 years diabetic duration (Powell et al 1977). Biochemical study also demonstrated reduced axoplasmic flow in •~ 15,000. experimental diabetic rats induced by streptozotocin (Schmidt et al 1975).…”
Section: Discussionmentioning
confidence: 96%
“…Basing on our observation, it allows us to consider that glycogen-like particles and electron homogeneous amorphous materials within the axons strongly suggest that metabolic abnormalities actually occur in the axons of the diabetic state. In experimental diabetic animals, accumulation of glycogen particles within mitochondria of the axons was found in the peripheral nerves of the rats rendered diabetic with alloxan for over 2 years diabetic duration (Powell et al 1977). Biochemical study also demonstrated reduced axoplasmic flow in •~ 15,000. experimental diabetic rats induced by streptozotocin (Schmidt et al 1975).…”
Section: Discussionmentioning
confidence: 96%
“…They explained that the delayed nerve conduction velocities detected in the diabetes rats were attributable to metabolic abnormalities of nodal gap, Schwann cell or axoplasm . On the basis of ultrastructural findings, Powell et al (1977) considered that the experimental diabetic neuropathy was induced by metabolic impairment of axons, Schwann cells and vessels, leading to segmental demyelination and axonal degeneration, in alloxan diabetes rats 2 years after the injection of alloxan. In the present study, our electron microscopic findings also suggested the impairment of both axons and Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…Usual presentation of diabetic neuropathy Other presentations of diabetic neuropathy or demyelination in peripheral nerves until long after nerve dysfunction is detected 44,45 , unless neuropathy is accompanied by other stressors, such as hypertension 46 . Nevertheless, many rodent models of diabetes exhibit indicators of Schwann cell dysfunction, including reduced expression of myelin-associated proteins 47 and Schwann cell-derived trophic factors, such as CNTF 19 and desert hedgehog 20,48 .…”
Section: Polyneuropathy Mononeuropathiesmentioning
confidence: 99%